DVDP 3 ロストウ オヨビ 6 ビイダコ ボーリング コアー チュウ ノ ニジ セイセイ コウブツ - 森川, 日出貴; モリカワ, ヒデキ; 湊, 一郎; ミナト, イチロウ; 小坂, 丈予; オサカ, ジョウヨ; 綿抜, 邦彦; ワタヌキ, クニヒコ; MORIKAWA, Hideki; MINATO, Ichiro; OSSAKA, Joyo; WATANUKI, Kunihiko (国立極地研究所, 1977)
P(論文) DVDP3(ロス島)および6(ビイダ湖)のボーリングコアー中の二次生成鉱物を採取し,粉末X線回折法により鉱物種の同定を行った.No. 3のコアー中には,calcite, aragonite, thenardite, milabilite, gypsum, nesquehonite, thaumasiteが認められた.No. 6のコアー中には,calcite, aragonite, gypsum, chlorite, laumontite, chabazite, sericite, montmorillonite, prehnite, flouriteが認められた.これらの鉱物の組み合わせおよび存在範囲より,生成当時の環境について推定を試みようとした.また ビイダ湖周辺の塩類析出物についても鉱物種の同定を行い,gypsum, calcite, thenardite, halite, sodium niter, prehnite, laumontite, chloriteが見出され,同所のボーリングコアー中のものとは異なっていることがわかった. The secondary minerals were collected from the drilling cores of DVDP 3 (Ross Island) and DVDP 6 (Lake Vida) and were investigated by the powder X-ray diffraction method. In No. 3 core the identified minerals are calcite, aragonite, thenardite, milabilite, gypsum, nesquehonite and thaumasite. In No. 6 core the identified minerals are calcite, aragonite, gypsum, chlorite, laumontite, chabazite, sericite, montmorillonite, prehnite and flourite. The mineral assemblage and the unusual distribution of some minerals may suggest the environments of the sedimentation of the rock and soil. The evaporites and secondary minerals around Lake Vida were also identified and gypsum, calcite, thenardite, halite, sodium niter, prehnite laumontite and chlorite were found. No correlation was noticed between the secondary minerals from No. 6 drilling core and those around Lake Vida. departmental bulletin paper